Pengaruh Store Layout, Interior Display Dan Promosi Terhadap Keputusan Pembelian (Studi pada Mahahsiswa Fakultas Ekonomi dan Bisnis Universitas Mataram) - Yaumil Akhiryananda (Postgraduate, University of Mataram, 2021)
The purpose of this study was to find out the influence of store layouts, display interiors, and promotions on purchasing decisions at the Café On Students of the Faculty of Economics and Business, University of Mataram. This research is included in quantitative research with survey methods. The type of data in this study is quantitative data. Data sources or information are obtained from primary and secondary sources. The data collection technique used in this study is in the form of primary data obtained from the results of respondents' responses to a list of statements in the form of questionnaires distributed to respondents. The population used is the person who ernah buys at Kamila Caffe. The sample taken was 100 people from the Faculty of Economics and Business (S1 Management). The data analysis technique used in this study is regression analysis. The results showed that: (1) Store layout factors affect consumer purchasing decisions at Kamila Caffe Mataram, meaning that if the store layout is getting better then the purchase decision is increasing. (2) The interior factor of the display is influential in the face of consumer purchase decisions at Kamila Caffe Mataram, meaning that if the interior display is getting better then the purchase decision is increasing. (3) Promoosi factor affects the consumer purchase decision at Kamila Caffe Mataram, meaning that if the promotion is getting better then the purchase decision is increasing